Piezoelectric transformer-based high conversion ratio interface for driving dielectric actuator in microrobotic applications. (12th September 2016) - Chen, Chen; Liu, Meng; Lin, Jun; Wang, Biao; Wang, Yanzhang
Dielectric actuators are utilized to convert electrical power into mechanical strain with considerable potential in microrobotic applications. However, critical challenges that need to be addressed include high-voltage interface with high conversion ratio, light weight, small size, and high power density. This study proposes a high piezoelectric transformer-based high conversion ratio interface that is integrated with a direct current/direct current high conversion ratio boost stage and a direct current/alternating current high-voltage driving stage. A piezoelectric transformer-based class-E zero voltage switching direct current/direct current interface is controlled by a hybrid pulse frequency modulation and pulse width modulation control strategies to obtain the desired high step-up ratio in the direct current/direct current stage. A half-bridge converter with special digital control algorithm in the direct current/alternating current stage is designed to convert high direct current voltage into arbitrary unipolar signal driving dielectric actuators. A prototype 23.3 g and 4 W interface has been fabricated for experimental validation to verify its ability to drive a 1 kV input dielectric actuator at 5 Hz in microrobotic applications.